PENGARUH TATA KELOLA PERUSAHAAN TERHADAP FINANCIAL DISTRESS (STUDI EMPIRIS PADA PERUSAHAAN ASURANSI UMUM DI BURSA EFEK INDONESIA PERIODE 2014-2022) - Utami , Rosalia Setya; Sufina, Lediana (Ibs Press, 2024)
This research aims to analyze and determine whether there is an influence of good corporate governance as proxied by managerial ownership, institutional ownership, independent board of commissioners, audit committee and auditor reputation on financial distress. The sample used in this research consisted of 10 general insurance companies that were listed on the Indonesian Stock Exchange for the period 2014-2022. The sampling technique in this research was purposive sampling and multiple linear regression methods. The research results show that managerial ownership and auditor reputation have a negative and significant effect, institutional ownership and an independent board of commissioners have a negative and insignificant effect on financial distress, while the audit committee has a positive and significant effect on financial distress.